Soil uptake of isoprenoids in a Eucalyptus urophylla plantation forest in subtropical China - Mu, Zhaobin; Zeng, Jianqiang; Zhang, Yanli; Song, Wei; Pang, Weihua; Yi, Zhigang; Asensio, Dolores; Llusià, Joan; Peñuelas, Josep; Wang, Xinming (Frontiers in Forests and Global Change, 2023)
The exchange of isoprenoids, which includes isoprene, monoterpenes, and sesquiterpenes, between ecosystem soils and the atmosphere plays a significant role in soil ecology and atmospheric chemistry. However, research on flux exchange rates in subtropical ecosystems has been limited, as previous studies have mainly focused on temperate and boreal environments. In this study, we aimed to quantify the exchange of isoprenoids between the soil (with or without surface litter) and the atmosphere in a subtropical Eucalyptus urophylla plantation forest during the daytime in the wet season of subtropical China. Additionally, we investigated the influence of soil and litter variables on the fluxes of isoprenoids. Our results unveiled the exchange of isoprene and 17 terpenoid compounds, comprising 11 monoterpenes and 6 sesquiterpenes, between the studied soils and the atmosphere. Interestingly, regardless of the presence of surface litter, the studied soils acted as net sinks for isoprenoids, with isoprene being the most absorbed compound (−71.84 ± 8.26 μg m−2 h−1). The removal of surface litter had a significant impact on the exchange rates of two monoterpenes (α-pinene and β-pinene), resulting in decreased fluxes. Furthermore, the exchange rates of isoprene were positively correlated with litter dry weight and negatively correlated with soil temperature. The higher exchange rates of monoterpenes and sesquiterpenes were associated with increased levels of soil respiration and the abundance of leaf litter. These findings suggest that, in the context of projected global warming scenarios, the capacity of subtropical soils to act as sinks for isoprenoids is expected to increase in subtropical China. These changes in sink capacity may have implications for regional-scale atmospheric chemistry and ecosystem functioning.